The Effect of a Physical Activity Program on Subjective Well-Being, Happiness and Problem-Solving Skills in Patients with Schizophrenia: A Randomized Controlled Trial. - Lok, Neslihan; Uzun, Gülten; Kahraman, Abdulselam; Lok, Sefa (Community Mental Health Journal, 2025)
The aim of this randomized controlled trial was to examine the effect of Physical Activity Program applied to patients with schizophrenia on subjective well-being, happiness and problem-solving skills levels. This study was conducted with a total of 86 individuals diagnosed with schizophrenia (43 intervention and 43 control) registered in a family health center. Subjective Well-Being Scale, the Short Form of the Oxford Happiness Questionnaire and Problem-Solving Inventory were used to collect the data at baseline and, post-intervention. Significant increases in subjective well-being, happiness, and problem-solving skills were found in the intervention group after the total of 12 weeks of the Physical Activity Program, which included walking and exercises, compared to the control group. Accordingly, it can be said that the Physical Activity Program is an effective method that increases subjective well-being, happiness and problem-solving skills. ClinicalTrials.gov Identifier number is NCT15976921 and date of registration is 21/11/2023, retrospectively registered.